On the mechanism of calcium‐dependent activation of NADPH oxidase 5 (NOX5). (20th December 2019) - Millana Fañanás, Elisa; Todesca, Sofia; Sicorello, Alessandro; Masino, Laura; Pompach, Petr; Magnani, Francesca; Pastore, Annalisa; Mattevi, Andrea
Abstract : It is now accepted that reactive oxygen species (ROS) are not only dangerous oxidative agents but also chemical mediators of the redox cell signaling and innate immune response. A central role in ROS‐controlled production is played by the NADPH oxidases (NOXs), a group of seven membrane‐bound enzymes (NOX1‐5 and DUOX1‐2) whose unique function is to produce ROS. Here, we describe the regulation of NOX5, a widespread family member present in cyanobacteria, protists, plants, fungi, and the animal kingdom. We show that the calmodulin‐like regulatory EF‐domain of NOX5 is partially unfolded and detached from the rest of the protein in the absence of calcium. In the presence of calcium, the C‐terminal lobe of the EF‐domain acquires an ordered and more compact structure that enables its binding to the enzyme dehydrogenase (DH) domain. Our spectroscopic and mutagenesis studies further identified a set of conserved aspartate residues in the DH domain that are essential for NOX5 activation. Altogether, our work shows that calcium induces an unfolded‐to‐folded transition of the EF‐domain that promotes direct interaction with a conserved regulatory region, resulting in NOX5 activation. Abstract : The N‐terminal domain (EF) of NADPH oxidase 5 contains four EF‐hand motifs and is the main player in this enzyme activation. In the absence of calcium, EF‐hands 3 and 4 are unfolded and the domain remains separated from the catalytic dehydrogenase domain (DH). In the presence of calcium, EF‐hands 3 and 4 acquire a structure and bind to the DH domain, activating the electron flow and production of reactive oxygen species.